A Thematic Analysis Exploration of Challenge-Based Learning Framework on Students of Academy X - Andi Setiawan Abadi; Serli Wijaya; Oviliani Y. Yuliana (Petra International Journal of Business Studies, 2023)
Education development has grown to accommodate various teaching and learning styles in recent years. Challenge-Based Learning, or CBL, is a learning framework conceptualized in 2006 at Apple's Classroom of Tomorrow Today that is built from the natural learning process of human beings. It recognizes that everyone comes equipped with their skills, knowledge, and interests, which opens the possibility for collaboration and teamwork across various knowledge and skill backgrounds. Academy X is an institution that builds its curriculum and activity on the foundation of challenge-based learning. One of the purposes of the Academy is to increase the employability level of the students after they graduate. This study uses Thematic Analysis of interview results with Academy students to see how the CBL process in the Academy is encouraging students to grow and become more successful even after the Academy, especially in facing their careers. In summary, this study confirms through the interview of 10 Academy students how the Challenge-Based Learning drives the development of Growth Mindset in terms of Professional capacity and Personal Development despite the existence of Hindrances along the way. As such, CBL facilitates students’ growth and development at the Academy for their future careers.